Degradação de solos sob pastagens na bacia do rio Alegre-ES: cobertura do solo e indicadores de qualidade - Monteiro, Edevaldo Castro (2015)
The inadequate pastures management caused their degradation that can occur gradually in different stages. These stages can be related to different degradation levels. Degraded pastures naturally have limitations such as low fertility, high acidity, hilly